Death obsession’s potential mediational role in the relation between pregnancy-related anxiety and prenatal obsessive-compulsive disorder - Bambo, Sadi Cordelia; Mashegoane, Solomon (SAGE, 2021)
The study investigated the mediator role of death obsession in the relationship between pregnancy-related anxiety and prenatal obsessive-compulsive disorder among pregnant women in the Capricorn district, South Africa. Two hundred and six conveniently selected respondents completed questionnaires individually. Statistically significant associations were found between pregnancy-related anxiety and death obsession, death obsession and prenatal obsessive-compulsive disorder, and pregnancy-related anxiety and prenatal obsessive-compulsive disorder (ps⩽.05). Analysis further showed that death obsession mediates the relationship between pregnancyrelated anxiety and both composite scores of a prenatal obsessive-compulsive disorder measure (Obsessive-Compulsive Inventory–Revised) and most of its components. The findings suggest that death obsession is a likely mediator that has to be studied further.
Journal article published in the journal of South African Journal of Psychology 2021, Vol. 51(3) 369–382
Keywords: Death obsession; Obsessive-compulsive disorder; Pregnancy-related anxiety; Pregnant women; Prenatal; Death; Obsessive-compulsive disorder; Pregnant women; Prenatal care